Reducing Waste in the Clinical Setting. Issue 6 (June 2020) - Wohlford, Sara; Esteves-Fuentes, Nathalia; Carter, Kimberly Ferren
Abstract : ABSTRACT: Nurses have the capacity and opportunity to alter their organization's environmental footprint. This article addresses how they can strengthen efficiency and environmental sustainability initiatives in their facilities by engaging in, monitoring, and supporting environmentally friendly clinical practices and programs at the point of care. Included are practical tips and examples of projects in which nurses identified sources of waste—the relaundering of unused linens; disposal of unused products; and improper sorting of pharmaceutical waste, recycling, and regulated medical waste—and realized significant cost savings as well as improved efficiency and environmental sustainability. Abstract : This article—winner of the 2019 Nurse Faculty Scholars/ AJN Mentored Writing Award—describes how nurses can promote workplace environmental sustainability initiatives in three areas: linen efficiency, supply waste reduction, and proper waste sorting.